El Cambio Repentino: Teachers’ Experiences with Reassignment to New Grade Level - Lagarto, Rowena; Punzalan, Randy D. (Edu Berkah Khatulistiwa, 2025)
The study explore the lived experiences of elementary teachers who underwent sudden teaching reassignments during the 2024–2025 school year. It involved 10 public elementary teachers who were abruptly assigned to new grade levels. Using a phenomenological-transcendental approach, data were gathered through interviews. Participants met specific criteria set by the researcher. Testimonies were analyzed using Qualitative Data Analysis (QDA), with support from a data analyst to verify transcripts and extract codes, subordinate themes, and superordinate themes. Findings revealed that teachers’ experiences began with shock and uncertainty. They encountered challenges in lesson planning, classroom management, and adapting instructional materials. Teachers needed to realign their methods with the new learners' needs. Over time, and with support from school heads, colleagues, and parents, they embraced El Cambio Repentino, refining their strategies and planning. The experience ultimately fostered professional development, strengthening both skills and motivation. From these teachers’ experiences, the researcher identified twenty (20) significant superordinate themes to describe their lived experiences. These include: emotional reactions to reassignment, anticipation of new challenges, difficulties during transition, changes in lesson planning and classroom management, internal and external factors as coping tools, support from school heads, colleagues, and parents, personal adaptation strategies to overcome challenges, past experiences as preparation, key realizations about adaptability and lifelong learning, motivation driven by passion and livelihood, understanding and acceptance of sudden change, self-perception and professional identity transformation, coping strategies for navigating transitions, instructional materials and management as major challenges, planning and collaboration as key response mechanisms, sustained motivation and professional commitment, intangible support systems such as emotional and moral support, synergy between personal growth and social connections, emotional resilience and professional advancement, and empowerment through adaptability in teaching assignments. These lived experiences led to the proposal of targeted professional development programs to support reassigned teachers. In the absence of formal DepEd guidelines, this study offers foundational insights for school leaders during transition planning.